Patent vitelline duct in an adult deceptively appeared to be acquired umbilical urachal sinus: a case report - Takano, M; Yamashita, S; Inuzuka, S; Suzu, H (Hinyokika kiyo. Acta urologica Japonica, 1995)
Here is presented a surprisingly rare case in a 40-year-old male who had patent vitelline duct by nature. However, his congenital disease appeared deceptively to be an acquired umbilical urachal sinus on the diagnostic evaluations including fistulography before surgery. The diagnosis was definitely confirmed after the successful surgical procedure. The principal reason why these diseases were indistinguishable was reviewed. The incidence of each disease and incidence of association with umbilical fistula in each disease were discussed. With regard to these incidences, we compared urachal anomalies with vitelline duct anomalies through reference of several literatures. This is the most unique event we have ever clinically experienced.